Microstructural evolution and nanoindentation of NiCrMoAl alloy coating deposited by arc spraying - P. Daram (2020)
© 2020 Elsevier B.V. Arc spraying is a flexible thermal spray coating that can be used in on-site applications. In this study, a NiCrMoAl alloy was coated onto a mild steel substrate by arc spraying. The cored wire feedstock and the deposited coating were extensively characterized by a combination of X-ray diffraction, scanning electron microscopy, focused ion beam microscopy and transmission electron microscopy. Vickers microhardness and nanoindentation were used to investigate the mechanical properties of individual phases in the coating. The results showed that the NiCrMoAl alloy cored wire feedstock primarily consisted of material in elemental form including Ni, Cr, Mo, Al, Si, and Ti, whilst the arc sprayed coating contained a solute-lean γ-Ni phase, a (Mo, Si)-rich γ-Ni phase, elemental Mo splat as well as Cr2O3, Al2O3, and SiO2 at intersplat regions, together with ≤100 nm spherical Al2O3 particles within the splats. Partitioning of Mo and Si into the γ-Ni phase was observed following the rapid solidification of the splat on deposition. The Vickers hardness analysis showed that the average overall hardness of the coating was about 3.65 ± 0.56 GPa. However, nanoindentation indicated that the highest hardness was in the γ-Ni splat regions, especially those containing a high concentration of solute. The microstructural evolution, as well as the structure and chemistry of the phases that affect mechanical properties in the coating are discussed in detail.